Faktor Keturunan dan Lingkar Pinggang terhadap Profile Gula Darah - Ni Luh Putu Yunianti Suntari Cakera; I Wayan Sukawana; I Made Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
This study analyzed the influence of heredity and waist circumference of the blood glucose profile (fasting, 2 hours PP, when blood glucose) in high school teenagers. Analytic survey research aimed at observing and analyzing the relationship between variables. The research design used cross sectional design. The linkage between genetic factors with fasting blood sugar levels, indicated by (1) Sig. alpha (0848 0.05). This means that Ho is accepted, genetic factors do not affect fasting blood sugar levels. (2) Sig. alpha (0.002 0.05). This means that Ho is rejected, genetic factors do not affect glucose levels darah2 pp hours. (3) Sig. alpha (0517 0.05). This means that Ho is accepted, genetic factors do not affect blood glucose levels for a while. The linkage between waist circumference factor with fasting blood sugar levels, indicated by (1) Sig. alpha (0327 0.05). It means that Ho is accepted, waist circumference do not affect fasting blood glucose levels. (2) Sig. alpha (0689 0.05). This means that Ho is accepted, waist circumference does not affect blood glucose levels 2 pp hours. (3) Sig. alpha (0322 0.05). This means that Ho is accepted, waist circumference does not affect blood glucose levels for a while.